Pengaruh Digital Marketing terhadap Pertumbuhan UMKM di Indonesia: Kajian Literatur Komprehensif - Aditya, Eriko (Maliki Interdisciplinary Journal, 2025)
This article aims to analyze the impact of digital marketing on the growth of small and medium enterprises (SMEs) in Indonesia through a comprehensive literature review. The study highlights the implementation of digital marketing strategies such as social media, e-commerce, and search engine optimization, and their effects on SMEs’ sustainability and expansion. Findings reveal that digital marketing enhances market access, budget efficiency, and customer loyalty. However, challenges such as limited digital literacy and restricted access to technology remain significant barriers. This article provides strategic recommendations to boost digital marketing adoption, supporting sustainable SME growth. Investment in the development of technological infrastructure, such as a wider and more stable internet network, should be a national priority. Further research is recommended to explore the application of innovative technologies such as data analytics and artificial intelligence in supporting digital marketing for MSMEs.